The German Version of Deregulation - And Beyond - Keller, Berndt (Relations industrielles / Industrial Relations, 1994)
The article deals with various deregulatory efforts in relation to labour relations and labour markets in Germany. The analysis differentiates between flexibilisation as a strategy of employers and deregulation as a collection of actions taken by the state, which currently provide the political flanks for employers' efforts towards flexibility. The central measures of German deregulation are described and criticized in theoretical and empirical perspective. A controlled form of flexibility instead of a market driven, non-controlled flexibility is given preferential treatment. Proposals are made for defensive, compensatory steps towards re-regulation; offensive, formative forms of regulation are discussed.